2017
DOI: 10.1088/1361-648x/aa8935
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Hubbard U on density functional-based predictions of BiFeO3properties

Abstract: Abstract.First principles studies of multiferroic materials, such as bismuth ferrite (BFO), require methods that extend beyond standard density functional theory (DFT). The DFT+U method is one such extension that is widely used in the study of BFO. We present a systematic study of the effects of the U parameter on the structural, ferroelectric and electronic properties of BFO. We find that the structural and ferroelectric properties change negligibly in the range of U typically considered for BFO (3-5 eV). In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 65 publications
(108 reference statements)
4
23
0
Order By: Relevance
“…While standard DFT methods are widely in use for such calculations, experimentally obtained outcomes of BiFeO 3 are more closely comparable to the DFT calculated values when Hubbard U parameter, a measure of effective on-site Coulomb interaction, is chosen carefully. [61][62][63][64][65] Experimentally obtained crystallographic parameters were rened by Rietveld method and their geometry was optimized prior to using them for DFT calculations. PDOS, electronic band structure and optical absorption spectra of both BFO bulk and BFO 160 nanoparticles were obtained via DFT calculations using GGA-PBE functionals.…”
Section: Optical Characterizationmentioning
confidence: 99%
“…While standard DFT methods are widely in use for such calculations, experimentally obtained outcomes of BiFeO 3 are more closely comparable to the DFT calculated values when Hubbard U parameter, a measure of effective on-site Coulomb interaction, is chosen carefully. [61][62][63][64][65] Experimentally obtained crystallographic parameters were rened by Rietveld method and their geometry was optimized prior to using them for DFT calculations. PDOS, electronic band structure and optical absorption spectra of both BFO bulk and BFO 160 nanoparticles were obtained via DFT calculations using GGA-PBE functionals.…”
Section: Optical Characterizationmentioning
confidence: 99%
“…All first-principles calculations, including initial structural optimizations of the NEB end-points, were completed with the GGA+U approximation 54,55 to densityfunctional theory which has been used effectively with BiFeO 3 13,56,57 . A U eff = 4 eV value was used to better treat the 3d electrons in Fe which has previously been benchmarked and utilized 13,58,59 . Repeating the calculations after altering the U eff value by 1 eV only changed the magnitude of the net magnetization, and did not alter the direction.…”
Section: B Bifeo3 Calculationsmentioning
confidence: 99%
“…However, a number of recent investigations [15,23] have demonstrated that choosing U eff parameter only to match the band gap, may introduce spurious effects for strongly correlated materials. For instance, Shenton et al [15] reported that a U eff value of 5 eV or larger is required to match the experimental band gap of BiFeO 3 . However, the ordering of the Fe d orbitals at the conduction band minimum of BiFeO 3 inverts for U eff > 4 eV.…”
Section: Introductionmentioning
confidence: 99%